2004
DOI: 10.2140/agt.2004.4.1253
|View full text |Cite|
|
Sign up to set email alerts
|

Homology stability for outer automorphism groups of free groups

Abstract: We prove that the quotient map from Aut(F n ) to Out(F n ) induces an isomorphism on homology in dimension i for n at least 2i + 4. This corrects an earlier proof by the first author and significantly improves the stability range. In the course of the proof, we also prove homology stability for a sequence of groups which are natural analogs of mapping class groups of surfaces with punctures. In particular, this leads to a slight improvement on the known stability range for Aut(F n ), showing that its ith homol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 10 publications
1
87
0
5
Order By: Relevance
“…Alternatively, we could have shown that S n (e, Z) is isomorphic to the complex V ± n,1 of [45] and use Proposition 2 of that paper.…”
Section: 2mentioning
confidence: 99%
“…Alternatively, we could have shown that S n (e, Z) is isomorphic to the complex V ± n,1 of [45] and use Proposition 2 of that paper.…”
Section: 2mentioning
confidence: 99%
“…For the symmetric group this was proved by Nakaoka ([Nak60]) and for Aut(F n ) by Hatcher and Vogtmann ([HV98a], [HV04]). The homology groups H k (Σ n ) are completely known.…”
mentioning
confidence: 88%
“…The groups Aut(F n ) are special cases of a more general series of groups A s n , studied in [HV04] and [HVW06]. We recall the definition.…”
Section: Corollary 12 the Groupsmentioning
confidence: 99%
“…Hatcher and Vogtmann [37] (see also Hatcher [35]) proved that the homology of Out F n stabilizes in a certain stable range. This is an analogue of Harer's stability theorem [34] for the mapping class group.…”
Section: Outer Automorphism Group Of Free Groupsmentioning
confidence: 98%